Biology and management affecting the decline of a black rhinoceros, Diceros bicornis minor (Linnaeus, 1758), population in Ndumo Game Reserve, KwaZulu-Natal, South Africa - Somers, Michael J. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.